2003
DOI: 10.1002/mrc.1231
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 2‐aryl‐1,3,4‐oxadiazoles by 15N and 13C NMR spectroscopy

Abstract: 15 N NMR data are a suitable and sensitive means for characterizing long-range electronic substituent effects. Additionally, 13 C NMR data for these compounds are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 11 publications
5
37
0
Order By: Relevance
“…In previous work, we have shown that the δ 15 N values are much more influenced by the resonance interactions (the ρ R parameters are about twice higher than the ρ I ones). [8] This confirms the low aromaticity of the 1,3,4-oxadiazole ring and a low coupling of oxygen atom lone electron pairs with the delocalized electron system, formed by phenyl ring and C N π -electrons.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…In previous work, we have shown that the δ 15 N values are much more influenced by the resonance interactions (the ρ R parameters are about twice higher than the ρ I ones). [8] This confirms the low aromaticity of the 1,3,4-oxadiazole ring and a low coupling of oxygen atom lone electron pairs with the delocalized electron system, formed by phenyl ring and C N π -electrons.…”
Section: Resultssupporting
confidence: 73%
“…They were about one-fifth of those detected for nitrogen atoms of oxadiazole ring. [8,9] This is a good experimental proof of the low aromaticity or even non-aromatic character of 1,3,4-oxadiazoles, postulated by some wileyonlinelibrary.com/journal/mrc authors on the basis of theoretical calculations and structural data. [12,13] The aromaticity indices published for unsubstituted 1,3,4-oxadiazole were 23.6-25.3 (benzene: 100; furan: 28.3-32.2; pyrole: 70.9-73.0).…”
Section: Theoretical Calculationsmentioning
confidence: 85%
See 2 more Smart Citations
“…2 Hammett correlations established the nature of electronic delocalization, and density functional theory calculations predicted chemical shifts and heterocyclic ring bond orders. We report, herein, the application of these methods to 5-phenyl-1,3,4-oxathiazol-2-ones (1a-1h), for which substituent effects have not previously been assessed.…”
Section: Introductionmentioning
confidence: 99%